Ultra-fine carbon nanosheets from coal oxidation for tri-functional improvement of carbon nanofiber fabrics. (5th January 2023) - Gan, Xuemeng; Yuan, Renlu; Zhu, Jiayao; Li, Qiqi; Tang, Tingting; Qin, Fuwei; Zhu, Linna; Zhang, Jun; Wang, Luxiang; Zhang, Su; Song, Huaihe; Jia, Dianzeng
Abstract: The development of advanced coal-based functional nanomaterials is of great significance for clean and effective utilization of coal resources. Herein, we report novel coal-based ultra-fine carbon nanosheets (UCNSs) prepared by chemical oxidation of bituminous coal with a high yield of 40.0 wt%. UCNSs show a lamellar size of 10–20 nm, mainly composed of 63.5 at.% carbon, 5.1 at.% nitrogen, and 31.4 at.% oxygen. The structural merits of suitable size distribution, enriched functional groups, and highly conjugated core enable the UCNSs showing a tri-functional reinforcement for carbon nanofibers prepared by electrospinning and carbonization. Thanks to the strong cross-linking effect and formation of entire conductive networks, the UCNS-embedded carbon nanofiber fabrics show 32.6 and 1.5 times improved mechanical strength and electrical conductivity, respectively, than the one without UCNSs. What's more, the exposed edges of UCNSs act as active sites for ultrafast capacitive energy storage, leading to the free-standing fabric with significantly improved capacitance and rate performance (191.2 F g −1 at 1 A g −1, 113.5 F g −1 at 50 A g −1 ) for aqueous supercapacitors. This work may provide a new thought for high-efficient and high-value-added utilization of coal resources. Graphical abstract: Ultra-fine carbon nanosheets with a high yield of 40.0 wt% were prepared through liquid-phase oxidation of bituminous coal, showing tri-functional (mechanical/electrical/electrochemical) reinforcement for carbon nanofiber fabrics. Image 1 Highlights: Ultra-fine carbon nanosheets with a high yield of 40 wt% were prepared from coal. The inlaid UCNSs show tri-functional reinforcement for carbon nanofiber fabrics. Exposed edges enable an ultra-fast pseudocapacitive energy storage ability.